Comparative Antioxidant Activity of Hibiscus sabdariffa and Ascorbic Acid on Ferrous Sulphateinduced Oxidative Stress in Clarias gariepinus. (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Lipid peroxidation is becoming a popular biological marker of oxidative stress. Hibiscus sabdariffa has been reported to serve as a herbal remedy for various disease conditions, but studies on its antioxidant activity and the extent to which it acts remain scarce. The antioxidant activity of H. sabdariffa aqueous extracts, an indigenous herbal drink, was compared with that of ascorbic acid in Clarias gariepinus (African catfish) with ferrous sulphate-induced oxidative stress. Eye tissue and blood samples were collected for the assay of reduced glutathione, malondialdehyde, lipid hydroperoxide and glucose levels. Administration of H. sabdariffa aqueous extract (0.27 ml/kg body weight) resulted in a significant reduction (p
Keywords: Oxidative stress; antioxidants; Hibiscus sabdariiffa, ferrous sulphate; Clarias gariepinus